2020
DOI: 10.1177/2048872620921598
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital cardiopulmonary resuscitation duration and neurological outcome after adult out-of-hospital cardiac arrest by location of arrest

Abstract: Background Little is known about the association between prehospital cardiopulmonary resuscitation duration for adults with out-of-hospital cardiac arrest and outcome by the location of arrests. This study aimed to investigate the association between prehospital cardiopulmonary resuscitation duration and one-month survival with favourable neurological outcome. Methods We analysed 276,391 adults aged 18 years and older with out-of-hospital cardiac arrest of medical origin before emergency medical service arriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A total of 4 studies were included in our meta-analysis [6][7][8][9]. Of them, we had 2 retrospective and 2 prospective cohort studies (1 from the United States, 1 from Europe, and 2 from Japan).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4 studies were included in our meta-analysis [6][7][8][9]. Of them, we had 2 retrospective and 2 prospective cohort studies (1 from the United States, 1 from Europe, and 2 from Japan).…”
Section: Resultsmentioning
confidence: 99%
“…In this issue, Kishimori et al reported that only 2.3% of 276,391 adults with OHCA in Japan survived with a favourable neurological outcome. 2 Beyond discussion, increased resuscitation attempts from both lay persons and professional caregivers in the prehospital setting can improve survival rates, but improved in-hospital care of the resuscitated OHCA patient is another important target. Intensivists and cardiologists have a common obligation here: do more research to improve outcome of the hospitalised OHCA patient.…”
mentioning
confidence: 99%